Volatile Hypertension Following Anterior Cervical Discectomy and Fusion: A Case Report. Issue 1 (24th February 2016) - Summers, Spencer H.; Sabeh, Karim; Gottlieb, Jonathan
Abstract : Case: A sixty-one-year-old man underwent anterior cervical discectomy and fusion (ACDF) from C4 to C7 for the treatment of cervical spondylosis. Postoperatively, the patient experienced paroxysmal surges in blood pressure with associated diaphoresis and anxiety that were difficult to control. He had additional episodes after discharge, requiring a second hospital admission. He was ultimately diagnosed with baroreflex failure syndrome and was managed with a three-drug regimen. He gradually improved and was symptom-free at seven months. Conclusion: Baroreflex failure syndrome should be considered in the setting of volatile hypertension following ACDF. Prompt recognition of this condition can lead to early referral to a specialist and may reduce patient morbidity.